A Psicanálise como contribuição para a formação docente: estudo colaborativo dos aspectos subjetivos e inconscientes da prática docente, com professores em formação inicial do Programa Residência Pedagógica Subgrupo Química - Souza, Débora Elisa de (2022)
Considering the challenges regarding pre-service science teacher undergraduate courses, there is a need to build spaces in which the future teacher in their initial training finds possibilities to develop as a more active teacher in their practice. The reflection process comprises teaching knowledge beyond academic training, also encompassing the constitution of personal values and beliefs, affective and emotional bonds between subjects and between the subject and the knowledge itself. Therefore, the purpose of this research is to know if there is a need to expand the reflection that the pre-service science teacher presents about teaching practice, about science teaching and about their own reflective process. To this end, the theoretical framework used to develop the discussions was the psychoanalytic and bionian of continence and content, as well as the group environment. A group of teachers in initial training of the “Pedagogical Residency – Chemistry Subgroup” project was observed. Based on phenomenology as a qualitative research method, teachers in initial training were asked about the subjective dimension of pre- service science teaching and practice in two main moments. The first one, based on the semi- structured interview carried out individually, and the second one, based on a group meeting that was named mediated conversation. Therefore, the descriptions that provided meaning to the theoretical framework used were chosen considering the data obtained from the interviews, direct observations of the meetings of the “Pedagogical Residency – Chemistry Subgroup” and the moments of mediated conversation carried out by the researcher. And based on the methodological guidelines of phenomenology, units of meaning were found. From them, after reduction movements were made, two main categories were raised, namely “Unconscious language of the teacher-student relationship” and “Pre-service science teaching”. In “Results and Discussions'' it was possible to infer that the Pedagogical Residency group establishes a basic assumption of dependence that coexists with the conscious proposals of the working group. When operating through dependence, the group expects the guidance counselor, as a leader, to signify their emotional experiences while bonding them to knowledge. The Residents present a reflective view of classroom work, as well as criticize the teacher who pays almost exclusive attention to disciplinary knowledge and content. They show confidence towards the teaching approach studied and practiced in the classes, being such approach of teaching the one by investigation. However, they show insecurity regarding the relationships of social interactions, as well as affective and subjective aspects that may show up in the classroom. The results allow us to say that an expansion of the process of guided reflection, addressing subjective matters of teaching practice, makes it possible to reduce gaps in the process of teacher training. The research is concluded by suggesting similar methods to the ones carried out by this research’s methodology, as a possibility to achieve one of the demands presented by the research subjects, to search for the experiential knowledge of teachers as a way of mirroring their actions in the classrooms, however, from now on, through a process guided by a mediator, which offers means to self-observation and analysis based on theoretical contributions.